Estrés laboral y clima organizacional en el comando de policía subzona Cotopaxi n° 5. - Caisaguano Ramos, Alejandro Patricio (2023)
The negative impact of work stress at the individual and organizational level is widely known, manifesting itself in reduced productivity, increased absenteeism and staff turnover, which affects the results and objectives of the organization. The present study in the Cotopaxi Sub-zone Police Command No. 5 focused on evaluating work stress and its link with the organizational climate. A descriptive, correlational and hypothetical methodology with a quantitative approach was used to analyze the data, covering 112 administrative employees through sampling. The instruments used were the Maslach Burnout Inventory - General Services Survey and the work climate measurement instrument developed by Koys and Decottis. The results showed low levels in the dimensions of burnout (93.75%), low in cynicism (95.45%) and high in professional effectiveness (91.07%). In relation to the organizational climate, a high level was found in the dimensions of autonomy (55.36%), cohesion (56.76%), trust (58.04%), support (42.34%) and innovation (62.50%), a medium level in recognition (53.57%) and equity (64.55%), and a low level in pressure (52.73%). In the Rho Sperman correlation, a coefficient of 0.075 was obtained, these results support the null hypothesis that postulates the inexistence of a relationship between work stress and organizational climate.